Bhikkhunīs’ Pregnancy: Inconsistency between the Narrative and the Garudhamma - ฉัตรสุวรรณ ธนสิทธิ์ (Journal of Buddhist Studies Chulalongkorn University, 2019)
This article aims to propose a solution to some question about the Sikkhamānā and the Garudhammas by referring to evidences in the scripture that the Buddha himself was quite flexible in some cases on the monastic regulations applied in relation to the status of SikkhamānāThe study focusing on the narrative of the cases of Bhikkhunīs’ pregnancy appearing in Tipitaka and commentaries found some questions about the Sikkhamānā which is an important status that the Buddha enacted for a woman wishing to ordain as a Bhikkhunī. The sixth rule of the eight Garudhammas (the chief rules) for women, which requires the Sikkhamānā to observe the six precepts strictly for two years before being considered a Bhikkhunī, is like an instrument for preventing a case of Bhikkhunīs’ pregnancy. The cases of Bhikkhunīs’ pregnancy in Tipitaka and commentaries seem to break or against this rule. They lead to the question of whether the sixth rule of the Sikkhamānā was applied before or after the ordination of the first group of Bhikkhunīs.